Сталінська ґендерна політика у добу «Великого терору» (1937–1938 рр.) - Вронська, Т. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2009)
Based on the unknown documents of Politburo of Central Committee of All-Russian Communist Party of Bolsheviks as well as of former Soviet security services, the author investigated the repressions against women, children and old men in 1937–1938.